Evolution of the largest glacier in Mexico (Glaciar Norte) since the 50s: factors driving glacier retreat. Issue 4 (2nd October 2019) - Cortés-Ramos, Jorge; Delgado-Granados, H.; Huggel, C.; Ontiveros-González, G.
ABSTRACT: The evolution of Mexican glaciers (19° N) in the climate context is poorly understood despite these glaciers are important indicators of regional climate change. The detailed patterns of glacier recession since the Little Ice Age (LIA) have exacerbated during the past years and decades. Their relationship to local and regional climate change needs further analysis. This study compares the changes of the largest glacier in Mexico, Glaciar Norte (GN), on Citlaltépetl Volcano with temperature, precipitation, and surface energy balance variations that were considered as part of climate forcing. Area, length, elevation, equilibrium line altitude (ELA), and thickness were calculated from historical and satellite data sets and a high-resolution Digital Elevation Model. The results showed that during the 1990s, prevailing warm and variable dry conditions enhanced the glacier retreat, triggering the disappearance of Jamapa glacier tongue. The glacier length has changed at the rate of −20.7 m a −1 since 1958. ELA varied from 4999 m a.s.l. in 1958–5228 m a.s.l. in 2017. A short period of snow accumulation from 2007 to 2009 was found when the annual temperature over GN showed a noticeable negative trend similar to that for the accumulated surface energy balance. The surface energy balance was conclusive on the response of GN to stability or accumulation periods. Finally, the long-term variation of temperature was the only factor found forcing the glacier retreat. Assuming that the retreat rate (−0.02 km a −1 ) and climate tendencies remained constant (0.1°C/decade), GN could disappear towards the middle of the twenty-first century.